2015
DOI: 10.1080/10548408.2014.896766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Service Fairness and Service Quality on Tourists’ Behavioral Intentions and Subjective Well-Being

Abstract: This study examined the effects of service fairness and service quality on tourists' behavioral intentions and subjective well-being (SWB) with the mediation of satisfaction. It conceptualizes SWB as a sociopsychological benefit that people receive from tourism activities in parallel with behavioral intentions to visit the destination treated as economic benefit. A self-administered questionnaire survey was conducted in Xiamen city of Fujian Province, China, and a valid sample of 541 tourists was used for data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 68 publications
(168 reference statements)
2
37
0
1
Order By: Relevance
“…Tourism is often referred to as a wellness industry since it plays an important role in the improvement of the SWB of residents living in, and visitors to, a travel destination. Among the various effects brought about by tourism, this improvement is considered a positive aspect of the social effect [76]. The SWB level of a tourist is naturally related to his/her personality and personal characteristics [71]; however, empirical analyses have also found that tourists' experiences (especially memorable tourism experiences) [75] and their perceptions of service quality and fairness [76] can significantly elevate their SWB.…”
Section: Subjective Well-beingmentioning
confidence: 99%
“…Tourism is often referred to as a wellness industry since it plays an important role in the improvement of the SWB of residents living in, and visitors to, a travel destination. Among the various effects brought about by tourism, this improvement is considered a positive aspect of the social effect [76]. The SWB level of a tourist is naturally related to his/her personality and personal characteristics [71]; however, empirical analyses have also found that tourists' experiences (especially memorable tourism experiences) [75] and their perceptions of service quality and fairness [76] can significantly elevate their SWB.…”
Section: Subjective Well-beingmentioning
confidence: 99%
“…This concern can be explained by an understanding of the relationship between tourism experience and its outcomes that affect the whole tourism industry. Satisfaction with tourism experience significantly influences the tourists' revisit intention and positive word of mouth that lead to economic gains for destination managers and socio-psychological benefits for tourists themselves [64]. Hence, satisfaction with tourism experience is acknowledged as a prominent issue for both public tourism organizations and destination marketing organizations and academic scholars in terms of investigating the main construct of tourism experience and important factors that can enhance the consumed tourism experience [17].…”
Section: Satisfaction With Tourism Experiencementioning
confidence: 99%
“…Some of them attempt to conceptualize the tourism experience while others focus on experience behaviors and types of experience [63,64]. With the emergence of different innovative technologies and growing popularity of social media use among tourists, more and more researchers are paying attention to the technology-enhanced tourism experience [65].…”
Section: Satisfaction With Tourism Experiencementioning
confidence: 99%
“…In relation to the limitations in the individual studies analysed, authors checked the limitations highlighted by the corresponding authors. These authors included as limitations the geographical coverage of the study limited to an area [53,60,62,66,70]; the specificity of the tourism facility (such as: thermal [62], sport event tourism [66] museums [53]) or service [60]; the sample size [66] and source [53]; the lack of qualitative data considered [59,71] and the restriction of the analyses made or techniques used [59,71]. Moreover, they also stressed the affective component of the variables studied [62], value perceptions [54] and subjective well-being [70] that emphasise the outcomes of this study towards research that propose and validate items to assess the individual perception of service quality, in particular, for tourists with special needs.…”
Section: Discussionmentioning
confidence: 99%